MANIFESTASI NILAI-NILAI BUDAYA DI BALIK LEKSIKON MAKIAN BERKATEGORI BINATANG DALAM BAHASA SUNDA - Budiarti, Dian; Faris, Ihsan Nur Iman (UNIVERSITAS PGRI YOGYAKARTA, 2024)
Playing an important role to carry out one of emotive functions in verbal communication, studies on swear words in various languages ​​have been conducted. However, the study based on an anthropolinguistic approach, especially in the context of Sundanese Language (BS), is still scant. This paper aims to present the results of the analysis of Sundanese swearing lexicons categorized as animal in terms of their lingual form and usage, as well as the manifestation of Sundanese cultural values reflected behind their meanings based on the procedures of literature review, observation, survey, and interviews. In general, the results of this study demonstrate that BS has at least 15 lexicons of swearing in the animal category. Based on their lingual form, the lexicon consists of a class of nouns which can be used in the form of words, phrases, and clauses. The meanings of these lexicons tend to be metaphorical, whose conceptions specifically reflect the Sundanese people's own perspective or thinking towards the related animals. Finally, the presence of various animal category of Sundanese swearing lexicons seems to describe its culture which is geographical in nature or influenced by the closeness of the people to the nature that spreads around them.